Important considerations in manufacturing of natural fiber composites: a review - Jaafar, Jamiluddin; Siregar, Januar Parlaungan; Mohd Salleh, Salwani; Mohd Hamdan, Mohd Hazim; Cionita, Tezara; Rihayat, Teuku (Springer, 2019)
The paper overviews the essential considerations in the manufacturing process of natural fber composites which infuence the performance of biocomposites. The evaluation of thermal properties of composites matrix and natural fber chemical composition and physical properties appears to be necessary as the initial screening factors before the manufacturing process of biocomposites. On the other hand, considerations on fber composition, type of manufacturing process and parameter used are seen as other crucial signifcant factors that need to be focused during the manufacturing of biocomposites. Moreover, the treatment used in the manufacturing process such as alkali treatment and coupling agent utilization should also be highlighted as additional important measures for better performance of biocomposites. In this review, all signifcant factors that infuence the performance outcome of natural fber composites are highlighted to provide the base-line source of literature for the manufacturing and production of composites sample. It is expected that the fndings from the present study could further enhance the performance of natural fber composites and able to become the preferred alternative or replacement for petroleum-based polymer in various industrial and commercial applications in the future.